Waste Selection Education in an Effort to Solve Waste Problems - Arifah, Risma Nur; Amirudin, Amin; Salsabila, Gardena; Arliyah, Regina Sukma; Abdillah, Moh. Rizky; Marza, Leonita; Al Idris, Andi Kasmi Maulidiyah (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Proper management of waste is crucial due to its potential to harm ecosystems and contribute to pollution. We should collectively initiate environmental stewardship by doing minor measures to safeguard it. Consequently, students at SDN 1 Sumberdem, Wonosari-Malang, are anticipated to acquire knowledge and engage in socializing regarding rubbish sorting through their participation in community service activities. The objective of this activity is to heighten students' awareness and motivate them to exhibit more attentiveness towards their immediate environment. It is crucial for children to comprehend the categorization of garbage, encompassing organic, inorganic, and B3 waste, alongside hazardous and toxic substances, and acquire the skills to manage them appropriately. Hence, it is imperative to socialize youth in order to deter archaic tendencies, such as discarding waste outdoors. Furthermore, it is imperative to provide them with instruction on the proper techniques for sorting, selecting, and categorizing waste, as well as on how to effectively operate a waste bank to make revenue. Engaging in games, presentations, and other interactive activities facilitates the process of socialization. There is an expectation that minor habits will propagate throughout the entire family and neighborhood, thus aiding in the mitigation of the environmental waste issue.